Role of management modalities in control and development of complications in diabetic patient ,in Thi-Qar province - H. Mohammad, Ahmed (University of Thi-Qar Journal of Science, 2019)
Background: Diabetes mellitus keeps on developing in worldwide pervasiveness and consume amount of health care resources. The management of diabetes incorporates capacity to change lifestyle, and physical activity.Objectives:Evaluate of management role (counting adherence) in control status and appraisal of adherence in control status of diabetic. Method: A cross-sectional design was used a convenience sample of 139 subjects with type 1, type 2 diabetes, ≥25 years old, included residents of the community in the city of Nasiriyah only registered in the Diabetes Center for both gender (62male and77female), between March and September 2016.Questionnaire sheet was used designed for collect data. Results: The study results indicated that the persons with a mean age of 50.01 ±12.4years, the cause of disease for participants’ more than half of them are hereditary (n=88;63.3%), Considering the uncontrolled more than half of them (n = 102 ; 73.4% ), less than half of them is within 10-14.9years duration of disease (n=46; 33.1%), more than half of them are used double hypoglycemic drug and poorly controlled in HbA1c (n= 111 ; 79.9%), (n =83 ;59.6%); respectively; there is a significant association of HbA1c with type of drug, significant association between determinants and duration of disease and type of drug with level of p-value ≤ 0.05. Conclusions. The majority of subjects haven’t their diabetes controlled; their low self-efficacy, and decline self-management. Therefore, strategies to promote self-management for patients are essential components of diabetes education programs, skill-building interventions are critical to be able to manage their diabetes.